Misuse of antibiotics in Iraq: A review of Iraqi published studies - Khulood Saadoon Salim; Atheer S. Alsabah; Hassanian S. Taghi (College of Pharmacy / Mustansiriyah University, 2022)
Misuse of antibiotics is one of the health problems worldwide. In Iraq, prevalence of self- medication with antibiotics increases resistant organisms, this will lead to bad impacts on health and economic aspects in the future. Aim of study is to review the published articles on the antibiotics misuse in Iraq, in   addition to assess the level of the population's knowledge towards   antibiotics misuse and the suggested recommendation to reduce this problem. Method: In this study 12 articles conducted in different regions of Iraq were reviewed to   assess antibiotic misuse in a period from 2014-2020.Results: The results demonstrated high prevalence of antibiotic misuse among Iraqi population ranging from (45%- 92%). In addition, poor knowledge among   population towards antibiotics misuse also reported. Bad attitudes of pharmacists and physicians regarding antibiotics prescribing and dispensing were registered. Conclusion:  The review focuses on important health issue in Iraq that effect on health & economic system. New legislations and restriction need to apply to limit this problem.